2000
DOI: 10.1021/jf0009910
|View full text |Cite
|
Sign up to set email alerts
|

Stilbene Content of MatureVitis viniferaBerries in Response to UV-C Elicitation

Abstract: A method using HPLC analysis has been used to compare the level of resveratrol and its derivatives, piceid, pterostilbene and epsilon-viniferin, in grapevine berries of three Vitis vinifera varieties. The concentration of these compounds has been evaluated in healthy and Botrytis cinerea infected grape clusters, both in natural vineyard conditions and in response to UV elicitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(146 citation statements)
references
References 22 publications
6
139
0
1
Order By: Relevance
“…They attributed the protective effect to a number of possible factors including PAL and peroxidase activity as well as the induction of 'stilbene-like phytoalexins' such as resveratrol (3, 5, 4′-trihydroxystilbene). Adrian, Jeandet, Douillet-Breuil, Tesson & Bessis (2000) showed that infection by B. cinerea could itself induce resveratrol formation and that UV irradiation increased resveratrol concentration in all the varieties of grape studied. However, where the grapes were already infected with B. cinerea, resveratrol induction was suppressed.…”
Section: Induced Effectsmentioning
confidence: 94%
“…They attributed the protective effect to a number of possible factors including PAL and peroxidase activity as well as the induction of 'stilbene-like phytoalexins' such as resveratrol (3, 5, 4′-trihydroxystilbene). Adrian, Jeandet, Douillet-Breuil, Tesson & Bessis (2000) showed that infection by B. cinerea could itself induce resveratrol formation and that UV irradiation increased resveratrol concentration in all the varieties of grape studied. However, where the grapes were already infected with B. cinerea, resveratrol induction was suppressed.…”
Section: Induced Effectsmentioning
confidence: 94%
“…We have been investigating the effects of phytochemicals on the prevention of cancer, using in vitro and ex vivo assay systems and have already reported that some food components, such as carotenoids, tea catechins, and resveratrol, have anti-proliferative and/or anti-invasive properties on hepatoma cells (Kozuki et al 2000;Zhang et al 2000a;Kozuki et al 2001). Pterostilbene (trans-3,5-dimethoxy-4 0 -hydroxystilbene) is a naturally occurring stilbenoid compound isolated from several natural plant sources including several types of grapes (Adrian et al 2000), blueberries (Rimando et al 2002), and the stem bark of several trees used in folk medicine such as Pterocarpus marsupium (Manickam et al 1997) and Guibourtia tessmanii (Fuendjiep et al 2002). Pterostilbene is an analogue of a well-studied stilbene, resveratrol.…”
Section: Introductionmentioning
confidence: 99%
“…Postharvest treatment of grape varieties with UV-C resulted in higher concentrations of stilbenes, such as E-resveratrol, piceatannol, viniferins and pterostilbene (Table 2, no. 4, 5) (Adrian et al 2000;Guerrero et al 2010a). Differences in concentration after UV-C irradiation depended on the variety and campaign, but not on the grape subspecies.…”
Section: Abiotic Postharvest Treatments Of Grapementioning
confidence: 93%